The Implementation Of Provisions In Article 16, Paragraph (1) Line M Of The Act No. 2 Of 2014 On The Notary’s Position In Pekalongan - Ade Alfriyan Rumrijono; Adimas Dirgantara; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This study examines the implementation of the provisions of Article 16 paragraph (1) line M UUJN in Pekalongan. This type of research is juridical empiric. These results indicate that the notary in Pekalongan has not implemented the provisions of Article 16 paragraph (1) line M UUJN. The legal consequences and responsibility for this violation is Notary agreement in question only has the strength of evidence as the Notary agreement under the hand and can be held accountability in civil and criminal law. Constraints implementation of these provisions are too large number of jobs of Public Notary , too small a value leads to low credit limit so that the Notary fees, and less understanding of the parties and the Notary of the provision itself.Keywords: Implementation; Provisions; Notary’s Position.